2017
DOI: 10.1007/s12325-017-0598-4
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Microstructure Analysis in Eyes with Diabetic Macular Edema Treated with Vitrectomy

Abstract: Current surgery helps DME patients to maintain VA and foveal structures. The results suggest that PROS length predicts visual outcome in DME patients following vitrectomy with ILM peeling and additional laser photocoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In addition, the length of the photoreceptor outer segment (PROS), where the visual pigment is concentrated and which can be reduced by inflammation and oxidative stress [17,19,21,[29][30][31][32], is also measurable in OCT images, although it has not been assessed in AMD. PROS length can be sensitive to pathological conditions involving photoreceptor cells; reduced PROS length is associated with worse visual outcomes in branch retinal vein occlusion [33], diabetic macular edema [34], central serous chorioretinopathy [35], and idiopathic epiretinal membrane [36].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the length of the photoreceptor outer segment (PROS), where the visual pigment is concentrated and which can be reduced by inflammation and oxidative stress [17,19,21,[29][30][31][32], is also measurable in OCT images, although it has not been assessed in AMD. PROS length can be sensitive to pathological conditions involving photoreceptor cells; reduced PROS length is associated with worse visual outcomes in branch retinal vein occlusion [33], diabetic macular edema [34], central serous chorioretinopathy [35], and idiopathic epiretinal membrane [36].…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Small gauge vitrectomy presents a proven treatment option in the current treatment of refractory DME. [ 16 , 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…The results of recent studies indicated that the changes in the microstructures of the foveal area are correlated with the visual acuity in eyes with DME [ 15 20 ]. For example, Mori et al suggested that the transverse length of the ellipsoid zone (EZ) of the photoreceptors was significantly correlated with the visual acuity improvement after ranibizumab injections in eyes with DME [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shiono et al indicate that PROS length was a predictive marker of postoperative visual acuities in patients with idiopathic epiretinal membrane [ 19 ]. Kogo et al suggest that PROS length was a predictor of visual outcome in patients with DME after vitrectomy [ 20 ]. However, a search of PubMed did not extract any publications that examined the correlation between the PROS length and outer retinal thickness with the visual acuity before and after IVA treatments in eyes with DME.…”
Section: Introductionmentioning
confidence: 99%